Postmortem urine concentration of N-terminal pro-brain natriuretic peptide in relation to the cause of death. (January 2020) - Takasu, Shojiro; Matsumoto, Sari; Kanto, Yuko; Kodama, Saki; Iwadate, Kimiharu
Highlights: Blood NT-proBNP is known to elevate in various medical conditions. Urinary NT-proBNP is reported to correlate with the blood level in living patients. We measured NT-proBNP in postmortem obtained urine in series of death cases. We observed a significant higher level in AMI, CHF, and sepsis cases. This is the first study to evaluate the utility of NT-proBNP in urine obtained postmortem. Abstract: The utility of biochemical marker analysis in forensic autopsy cases is still uncertain due to the postmortem changes which they undergo. Thus, research is required to elucidate alternative samples and biochemical markers which are less affected by postmortem changes. Levels of N-terminal pro-brain natriuretic peptide (NT-proBNP) are known to be elevated in congestive heart failure (CHF), acute myocardial infarction (AMI), and sepsis patients. Although NT-proBNP is reportedly excreted into the urine, no study has previously evaluated the diagnostic efficacy of urinary concentrations in a forensic setting. The aim of this study was to evaluate the diagnostic efficacy of NT-proBNP concentration in urine obtained postmortem in a series of forensic autopsy cases. Methods: Urinary NT-proBNP was measured in 36 AMI, 10 CHF, and 19 sepsis cases, and in 124 control cases (all with postmortem interval [PMI] < 72 h). Results: Urinary NT-proBNP was significantly higher in AMI, CHF, and sepsis cases than in control cases. Cut-off values for diagnosing AMI, CHF, and sepsis-related fatalities were 98 (sensitivity, 55.6 %; specificity, 73.4 %), 1050 (sensitivity, 80.0 %; specificity, 94.4 %), and 363 pg/mL (sensitivity, 84.2 %; specificity, 85.5 %), respectively. Furthermore, we subdivided the control cases according to the death process as either acute death (87 cases) or prolonged death cases (37 cases). Although urine NT-proBNP of CHF and sepsis cases were significantly higher compared with both cases, the concentration in the AMI cases were significantly high only when compared with the acute death cases. Conclusion: This study is the first to elucidate the diagnostic utility of NT-proBNP measurement in urine obtained postmortem in a series of causes of death. This study suggests the diagnostic efficacy for AMI, CHF, and sepsis-related fatality in cases in which the PMI was within 72 h.